Individuality and Entanglement: The Moral and Material Bases of Social Life - Robson, Arthur (Journal of Economic Literature, 2024)
Arthur Robson of Simon Fraser University reviews “Individuality and Entanglement: The Moral and Material Bases of Social Life” by Herbert Gintis. The Econlit abstract of this book begins: “Analyzes human social life as a game with rules, with people as players in this game and politics as the arena in which these rules are affirmed and changed.”